HIFs, angiogenesis, and cancer. Issue 5 (14th March 2013) - Yang, Yongzhi; Sun, Mingjuan; Wang, Lianghua; Jiao, Binghua
Abstract Tumor hypoxia was first described in the 1950s by radiation oncologists as a frequent cause of failure to radiotherapy in solid tumors. Today, it is evident that tumor hypoxia is a common feature of many cancers and the master regulator of hypoxia, hypoxia‐inducible factor‐1 (HIF‐1), regulates multiple aspects of tumorigenesis, including angiogenesis, proliferation, metabolism, metastasis, differentiation, and response to radiation therapy. Although the tumor hypoxia response mechanism leads to a multitude of downstream effects, it is angiogenesis that is most crucial and also most susceptible to molecular manipulation. The delineation of molecular mechanisms of angiogenesis has revealed a critical role for HIF‐1 in the regulation of angiogenic growth factors. In this article, we review what has been described about HIF‐1: its structure, its regulation, and its implication for cancer therapy and we focus on its role in angiogenesis and cancer. J. Cell. Biochem. 114: 967–974, 2013. © 2012 Wiley Periodicals, Inc.